Lee de Forest King of Radio, Television, and Film - Adams, Mike.; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
Lee de Forest, Yale doctorate and Oscar winner, gave voice to the radio and the motion picture. Yet by the 1930s, after the radio and the Talkies were regular features of American life, Lee de Forest had seemingly lost everything. Why? Why didn$1 (Bt he receive the recognition and acclaim he sought his entire life until years later in 1959, when he was awarded an Oscar? A lifelong innovator, Lee de Forest invented the three-element vacuum tube which he developed between 1906 and 1916 as a detector, amplifier, and oscillator of radio waves. As early as 1907, he was broadcasting music programming. In 1918, he began to develop a system for recording and playing back sound by using light patterns on motion picture film. In order to promote and demonstrate his process he made hundreds of short sound films, found theatres for their showing, and issued publicity to gain audiences for his invention. While he received many patents for this technology, he was ignored by the film industry. Lee de Forest, King of Radio, Television, and Film is about the process of invention$1 (Bhow inventors really get ideas and how every inventor learns that they must know the work of those who came before, and why the myth of the lone inventor and the (3z(BAha! moment(3y (Bis largely a fiction. Through his inventions, Lee de Forest made possible the mass entertainment media we enjoy today. This is his story.s
Chapter 1 Born to Invent -- Chapter 2 The Race for Wireless -- Chapter 3 The Meaning of the Audion -- Chapter 4 California Days -- Chapter 5 Radio$1 (Bs Arrival -- Chapter 6 Phonofilm, the Promise -- Chapter 7 Phonofilm, the Realization -- Chapter 8 Phonofilm, the Rejection -- Chapter 9 Phonofilm, the Lawyers -- Chapter 10 Lesson and Legacy.s
Keywords: Engineering; Science -- History; Multimedia systems; Mathematics; Performing arts; Humanities; Engineering; Signal, Image and Speech Processing; Multimedia Information Systems; History of Science; Popular Science in Mathematics/Computer Science/Natural Science/Technology.; Cultural Heritage; Performing Arts